2018
DOI: 10.3386/w24803
|View full text |Cite
|
Sign up to set email alerts
|

Financial Fraud among Older Americans: Evidence and Implications

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w24803.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…Of those, 5% were investment fraud, 4% were prize or lottery fraud, and 30% were others who used or attempted to use the respondent's accounts without permission. Despite these, DeLiema et al (2018b) found no single, reliable predictor of fraud victimization.…”
Section: The Health and Retirement Studymentioning
confidence: 92%
See 2 more Smart Citations
“…Of those, 5% were investment fraud, 4% were prize or lottery fraud, and 30% were others who used or attempted to use the respondent's accounts without permission. Despite these, DeLiema et al (2018b) found no single, reliable predictor of fraud victimization.…”
Section: The Health and Retirement Studymentioning
confidence: 92%
“…The same authors also published another study in 2018 that narrowed in on the types of fraud experienced by respondents of the 2016 HRS wave (DeLiema et al 2018b). The vast majority of respondents reported no fraud over the past five years.…”
Section: The Health and Retirement Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Armed with an evidence-supported developmental model of the trajectory of change in emotional processing in the elderly, we may be able to treatment, and refusal of care by family members or health care professionals. The decline of cognitive function in the elderly with its associated defense mechanisms may also make the elderly more vulnerable to fraud and financial exploitation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, information can have high returns at older ages: for example, more financially literate individuals are better prepared to deal with the intricacies of social insurance eligibility for long‐term care needs (Liu and Mukherjee ). Financial and health literacy can also reduce vulnerability to financial fraud and other forms of financial abuse, which are significant problems in present day (DeLiema et al ; DeLiema and Conrad ).…”
Section: Introductionmentioning
confidence: 99%